Excluding subarachnoid haemorrhage within 24 hours: to LP or not to LP?. (4th March 2021) - Chee, Carolyn; Roji, Akmal Mohamad; Lorde, Nathan; Divyateja, Hrushikesh; Dow, Graham; Shah, Jagrit; Chokkalingam, K.
Abstract: Background and purpose: Subarachnoid haemorrhage (SAH) is a potentially life-threatening cause of acute headache. Current conventional practice in the United Kingdom (UK) is for head computed tomography (CT) followed by cerebrospinal fluid (CSF) xanthochromia analysis if the head CT is normal. However, with increasing radiological accuracy, head CT alone may be sufficient to exclude SAH without requiring CSF xanthochromia for confirmation. This study aims to determine whether CSF xanthochromia is still required to confirm exclusion of SAH after normal head CT within a tertiary referral centre. Methods: Data was obtained from Nottingham University Hospitals (NUH) NHS Trust databases on 999 patients presenting with symptoms suspicious of SAH from 2012 to 2015. All patients had CSF xanthochromia analysis when head CT was normal or inconclusive for suspected SAH. Results: A total of 179 patients were diagnosed with SAH (17.9%). 176 patients were diagnosed radiologically and 3 patients required further investigations. The 3 of the 802 patients who underwent lumbar puncture (LP) and were identified as having had SAH presented more than 24 hours after ictus. When stratified according to the time of presentation, a normal CT head was observed in those who presented within 24 hours from ictus (sensitivity of 100% [95% CI 92.5–100] and negative predictive value of 100% [97.2–100]). Conclusion: Within a tertiary referral centre for SAH, a normal head CT has a very high negative predictive value to exclude SAH when carried out within 24 hours from ictus provided a 3rd generation CT scanner is utilised, and the scan is reported by a neuroradiologist. CSF xanthochromia analysis in this cohort may still be indicated in those presenting with a high clinical suspicion of SAH and in hospital settings where neuroradiologists or 3rd generation CT scanners are not easily accessible.